Monitoring Kebocoran Gas LPG Menggunakan Mikrokontroler Berbasis Website - S Nur Muslimah; Andre Ade Irawan (Institut Teknologi Adhi Tama Surabaya, 2023)
This study describes the design of an LPG gas leak monitoring system using a website-based microcontroller. Minister of Energy and Mineral Resources Decree No: 1971/26/MEM/2007 dated 22 May 2007 concerning the conversion of petroleum, namely kerosene, into LPG gas. Much of the LPG gas used by the public has experienced a decline in the quality of gas cylinders, due to the lack of supervision of gas cylinder products so that it can be dangerous for the community. Rusty, damaged, dented gas cylinders were found, and rubber seals on the gas cylinders were damaged, which in turn could cause LPG gas cylinders to leak and even explode. Based on these problems, in this study a gas leak monitoring and control system was created using the MQ2 sensor and microcontroller. The MQ2 sensor will detect a gas leak from the volume of gas in the room. If the gas value in the room is 300 ppm, the relay will turn on and will turn on the exhaust fan. Then wemos d1 mini will display this value in the database and will be displayed on the website. This research is expected to reduce the possibility of gas cylinders exploding and fires targeting kitchens or restaurants and other places that use LPG cylinders.